2016
DOI: 10.1002/stem.2278
|View full text |Cite
|
Sign up to set email alerts
|

Human Salivary Gland Stem Cells Functionally Restore Radiation Damaged Salivary Glands

Abstract: Adult stem cells are often touted as therapeutic agents in the regenerative medicine field, however data detailing both the engraftment and functional capabilities of solid tissue derived human adult epithelial stem cells is scarce. Here we show the isolation of adult human salivary gland (SG) stem/progenitor cells and demonstrate at the single cell level in vitro self-renewal and differentiation into multilineage organoids. We also show in vivo functionality, long-term engraftment, and functional restoration … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
190
1
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 190 publications
(211 citation statements)
references
References 52 publications
3
190
1
2
Order By: Relevance
“…Pringle et al in 2016 (65) , showed engrafment and functional capabilities of human adult epithelial stem cells in salivary gland demonstatrd in vitro self renewal and differentiation into multilineage organoids. He also showed in vivo functionality, long term engrafment and functional restoration in Xenotransplantation model.…”
Section: Salivary Gland Regeneration After Radiation Therapy:-mentioning
confidence: 99%
“…Pringle et al in 2016 (65) , showed engrafment and functional capabilities of human adult epithelial stem cells in salivary gland demonstatrd in vitro self renewal and differentiation into multilineage organoids. He also showed in vivo functionality, long term engrafment and functional restoration in Xenotransplantation model.…”
Section: Salivary Gland Regeneration After Radiation Therapy:-mentioning
confidence: 99%
“…Since human salispheres do contain KIT+ cells, there is a potential for future clinical use of KIT+ cell subpopulations [22]. Recently, Pringle and others [13] have successfully transplanted human salispheres into irradiated mice restoring the salivary flow, particularly when these salispheres were positively selected for KIT. However, the subpopulation of KIT+ cells in human SGs is very limited being less than 0.4% of the total population in younger adults, and this number substantially decreases with aging [13].…”
Section: Salivary Stem/progenitor Cells and Their Secretomementioning
confidence: 99%
“…Recently, Pringle and others [13] have successfully transplanted human salispheres into irradiated mice restoring the salivary flow, particularly when these salispheres were positively selected for KIT. However, the subpopulation of KIT+ cells in human SGs is very limited being less than 0.4% of the total population in younger adults, and this number substantially decreases with aging [13]. Moreover, these salispheres have a restricted in vitro self-renewal and proliferative capacities that confines their growth to 2-3 population doublings at earlier passages (P1–P4) [13].…”
Section: Salivary Stem/progenitor Cells and Their Secretomementioning
confidence: 99%
See 1 more Smart Citation
“…However, the size of the submandibular and sublingual glands and location of their main ducts make stem cell sparing approaches challenging. Therefore, the findings that in vitro expandable stem cells (6) representing a critical target localized in anatomical similar regions in different glands in various species (1,2) suggests that transplantation of stem cells may be a viable approach to rescue e.g., the submandibular gland (6,7).…”
mentioning
confidence: 99%